Coagulation process for fluoride removal by comparative evaluation of alum and PACl coagulants with subsequent membrane micro-filtration. (2017) - Agarwal, Madhu; Dubey, Swati; Gupta, A.B.
In this paper, the fluoride removal efficiency of the two coagulants was compared in batch and continuous mode. The optimum dosage for PACl was 438–2, 410 ppm and 275–1, 510 ppm for alum for treating fluoride concentrations of 2–10 ppm. The results showed that PACl was equally effective in bringing the fluoride level within the acceptable limit (1.5 ppm) in water with half lime dosage, compared to alum. Residual fluoride in dissolved form was found to be 0.66–0.83 for alum and 0.78–0.99 for PACl. It was also observed that residual aluminium decreases from 0.46 (alum) to 0.34 (PACl) for 4 ppm of initial fluoride concentration. After subsequent microfiltration, residual Al was found to be 0.182 ppm (alum) and 0.143 ppm (PACl). From the results, it can be stated that the residual turbidity and TDS for alum, as compared to PACl. Thus, switching the process to continuous mode using PACl coagulant with a sequential microfiltration, could meet quality criteria for drinking water.